Peran Perlindungan Hukum Dalam Mengurangi Dampak Kekerasan Terhadap Anak Dalam Lingkungan Keluarga - Tia Zahara; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Violence against children within the family environment is an urgent legal issue that can severely damage children's physical and emotional development. The objective of this study is to explore the role of legal protection in mitigating the impact of violence against children. The methodology employed involves qualitative analysis of existing legal regulations, including Law No. 35 of 2014 on Child Protection, along with interviews with legal practitioners and child psychologists. The results indicate that despite the existence of an adequate legal framework, implementation on the ground still faces significant challenges, such as social stigma and a lack of resources. This study recommends the need for legal education and community awareness to strengthen child protection within families.